Detection of infectious bursal disease virus by reverse transcription/polymerase chain reaction in chicken - Ozbey, G.; Ertas, H. B.; Kilic, A.; Muz, A. (Indian Veterinary Journal, 2006)
Sensitive and specific molecular methods have been used to diagnose and characterise infectious, bursal disease (IBD) infection in chicken in recent years (Lee et al., 1992; Wu et al., 1992; Stram et al. 1994). A reverse transcriptase/polymerase chain reaction (RT/PCR) to amplify the viral genome has been used successfully to amplify the IBDVirus VP2 gene region with oligonucleotide primers selected from the highly conserved region (Jackwood and Jackwood, 1994; Jackwood and Jackwood, 1997; Jackwood and Nielsen, 1997; Cao et al., 1998). The aim of this study was to detect lBDVirus in bursal samples collected from chicken flocks showing clinical symptoms of IBD in Elazig region by a RT/PCR using specific primers to the VP2 gene.
Keywords: Strains; Assay; Virulent; Rna